2020
DOI: 10.2967/jnumed.119.238808
|View full text |Cite
|
Sign up to set email alerts
|

MITIGATE-NeoBOMB1, a Phase I/IIa Study to Evaluate Safety, Pharmacokinetics, and Preliminary Imaging of 68Ga-NeoBOMB1, a Gastrin-Releasing Peptide Receptor Antagonist, in GIST Patients

Abstract: Introduction: Gastrin Releasing peptide receptors (GRPRs) are potential molecular imaging targets in a variety of tumors. Recently, a 68 Ga-labelled antagonist to GRPRs, NeoBOMB1, was developed for PET. We report on the outcome of a Phase I/IIa clinical trial (EudraCT 2016-002053-38) within the EU-FP7 project Closed-loop Molecular Environment for Minimally Invasive Treatment of Patients with Metastatic Gastrointestinal Stromal Tumours ('MITIGATE') (grant agreement number 602306) in patients with oligometastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…[ 68 Ga]Ga-NeoB strongly visualized the prostate primary tumor but also metastatic foci such as liver and bone metastases, with high lesion to background ratio [ 24 ]. Furthermore, a recent Phase I/IIa clinical study was concluded assessing the safety, tolerability, pharmacokinetics and dosimetry of [ 68 Ga]Ga-NeoB in GIST patients (MITIGATE clinical trial, NCT02931929) [ 33 ]. Another important pre-clinical finding was the fact that the injected mass of NeoB constitutes a key parameter since it impacts the retention in off-target organs and therefore the dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…[ 68 Ga]Ga-NeoB strongly visualized the prostate primary tumor but also metastatic foci such as liver and bone metastases, with high lesion to background ratio [ 24 ]. Furthermore, a recent Phase I/IIa clinical study was concluded assessing the safety, tolerability, pharmacokinetics and dosimetry of [ 68 Ga]Ga-NeoB in GIST patients (MITIGATE clinical trial, NCT02931929) [ 33 ]. Another important pre-clinical finding was the fact that the injected mass of NeoB constitutes a key parameter since it impacts the retention in off-target organs and therefore the dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…It could be suggested, that endoradiotherapy with [ 177 Lu]Lu/[ 225 Ac]Ac-NeoB would be an additional, more specific therapeutic option to SIRT, IRE or MWA in patients with high GRPR-expressing lesions in multiple organs. However, it should be taken into account that if tumorous lesions known from morphologic imaging do not show a [ 68 Ga]Ga-NeoB uptake, this might also be related to low GRPR expression (Gruber et al, 2020). It is well known that GIST have a wide spectrum of mutations, some of it with very low incidence (Lasota et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies the labeling method for [ 68 Ga]Ga-NeoB proved to be high yielding and stable (Pretze et al, 2021;Lau et al, 2019). As known from the first clinical study, [ 68 Ga]Ga-NeoB might have significant impact on the detection and treatment of GRPR expressing tumors such as like GIST (Gruber et al, 2020). Labeled with therapeutic radionuclides the peptide NeoB could also be useful for the treatment of imatinib-resistant GIST (Baratto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…showing no [ 68 Ga]Ga-NeoB uptake after SIRT therapy. The reason for the higher uptake in segment II/III could be a possible increased GRPR expression in growing GIST lesions or in metabolic active phases [29]. [29].…”
Section: Discussionmentioning
confidence: 99%